Primary Ewing’s sarcoma of sphenoid sinus: A case report and literature review - Wu, Kunpeng; Zhu, Xiaoyan; Li, Yan; Wen, Daxiong; Wu, Huiyu; Lai, Yanzhen; Li, Yun; Wu, Jian; Liu, Zhuoxing (Frontiers in Oncology, 2022)
Background Primary Ewing’s sarcoma of sphenoid sinus, observed in children and adolescents, is an extremely rare malignancy. Such rarity makes the imaging features and treatment strategies for Ewing’s sarcoma of sphenoid sinus unclear. This study aimed to offer guidance for treating this very disease by describing a patient with a rare primary Ewing’s sarcoma of sphenoid sinus and reviewing the available data in the literature. Case description A case of Ewing’s sarcoma in sphenoid sinus treated with multidisciplinary treatment approaches, including tumor resection, radiotherapy, chemotherapy, and antiangiogenic therapy, was presented in this study. Moreover, literature for Ewing’s sarcoma in the head was systematically searched, and two cases in the sphenoid sinus and five cases in the sphenoid bone were identified. Furthermore, the clinical features, imaging findings, pathological characteristics, treatment, and prognosis were summarized. Conclusion Tumor resection combined with radiotherapy and chemotherapy may provide favorable results for patients with Ewing’s sarcoma of sphenoid sinus and bone. However, more reports are still necessary to further clarify optimal management.